Translocacion del agente causal del anublo bacterial de la yuca (Manihot esculenta Crantz) en los tejidos del hospedero - Takatsu, A.; Lozano, J.C. (1975)
Studies on the translocation of the causal agent of cassava bacterial blight (considered to be a biotype of Xanthomonas manihotis) within the host tissues showed that this pathogen moves mainly through the xylem tissue. The primary stem symptoms appear on the green portion of the stem, but their appearance depends on varietal susceptibility and the water content of the soil. Spray inoculations gave even infection; this method appears to be useful for screening for resistant varieties. A new shoot-rooting method, which shortens the rooting period as compared with other reported methods, was devised; no failures to root occur. (AS)